The UK Prospective Diabetes Study - Turner, R; Holman, R (1996)
The Diabetes Control and Complications Study has shown that improved blood glucose control would delay the progress of microvascular complications of diabetes. However, in patients with non-insulin-dependent diabetes mellitus, the major morbidity and mortality arises from premature cardiovascular disease. It is uncertain whether therapy aimed to improve diabetes control will prevent cardiovascular complications, and whether the available therapies, sulphonylurea, biguanides or insulin, may even have long-term deleterious side-effects. The UK prospective Diabetes Study started in 1997 and is evaluating whether long-term therapy to improve control would be advantageous in clinical practice. The study has demonstrated that it is difficult to maintain improved glucose control because of the progressive β-cell dysfunction. The study is also evaluating whether improved control of hypertension would be advantageous. The progress of the study is summarized. The results are expected to be published in 1998.